Estudo e análise da eficiência de inversores solar fotovoltaico - Alves, Thiago Flosino (Universidade Federal do Tocantins, 2019)
Nowadays with constant development of technology, more and more subjects such as energy efficiency and renewable energies are discussed every day, cause energy efficiency means less losses of resources and saving for both concessionaires and consumers. The development of electronic technologies enabled to have a great advance in the control of processes related to electricity, this control allows the manipulation of electrical signals, lowering or increasing the amplitude of the signal, and the conversion between direct and alternate signals. This work is about the interference of temperature in the efficiency of inverters on grid at the region of the southern master plan at Palmas. Electronic devices are designed to operate on a safety temperature which it must not be exceeded due to operating instability, reduced life or even serious failure. Information on electricity conversion efficiency and losses caused by temperature rise is important for the implementation of a possible optimization in inverters when it applied to on grid photovoltaic systems.